Klitih and Adolescent Violence in Yogyakarta: A Criminological and Legal Analysis of “Teen” Delinquency from Socialisations - Zhavia Lysandra Hakim (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
Delinquent behaviour during adolescence is a widely recognised phenomenon not only among criminologists but also within the broader public consciousness. This issue transcends cultural boundaries and manifests uniquely in different regions—including Indonesia. A particularly alarming form of youth delinquency has emerged in Yogyakarta under the term klitih, a Javanese word that originally described the harmless act of aimless wandering at night. Over time, however, klitih has undergone a semantic transformation and is now associated with brutal acts of street violence perpetrated predominantly by young individuals. These acts typically involve unprovoked attacks on unsuspecting residents, motivated not by material gain but by the sheer satisfaction derived from inflicting harm. Perpetrators of klitih are generally adolescents and young adults aged between 12 and 24 years old. They often operate in groups, using motorcycles to move swiftly and anonymously through urban areas. Despite their age, the violent nature of these actions has been widely described as barbaric and malevolent. The consequences are severe, ranging from serious physical injuries to fatalities. The phenomenon raises urgent and complex questions: What drives these young individuals to commit such horrifying acts of violence? What social, psychological, or structural factors contribute to the normalization of such behaviour? And more importantly, can this alarming trend be addressed and resolved effectively through legal and criminological intervention? This paper seeks to explore these questions through the analytical frameworks provided by several prominent criminological theories—such as Differential Association Theory, Social Control Theory, and Strain Theory—in order to better understand the roots of klitih and propose evidence-based approaches to its prevention and suppression within the context of Indonesian criminal law and juvenile justice.